Keamanan Jaringan Hotspot Mikrotik Menggunakan Metode Otentikasi Pengguna dengan Captcha dan IP-Binding Untuk Filtering User - Muhammad Rayza; Ari Usman; Arif Budiman (LKP Unity Academy, 2023)
One of the most common services provided for internet users is a hotspot network. This hotspot functions as a public area equipped with wireless network access. Numerous hotspot locations are available, with some even offering free access, allowing everyone to enjoy this service without any charges. However, security concerns are a significant focus in utilizing hotspot facilities in public zones due to the open nature of these places. Additionally, the use of hotspot networks also has a drawback - the existence of security vulnerabilities due to a lack of administrative attention. Based on findings from existing literature, an effective approach to enhancing wireless security involves user authentication through CAPTCHA and IP-binding methods for user filtration. It is anticipated that this user authentication method can optimize hotspot network security, ensuring that only authorized and registered individuals can access the service.